Gerenciamento de resultados contábeis em oferta pública de ações - Domingos, Sylvia Rejane Magalhães (2014)
The general objective of this study was to investigate the practice of corporate earnings management in the period surrounding a public offering. The study was based on quarterly financial data collected from a sample of firms traded on BM&FBovespa making public offerings between 2004 and 2013. The practice of earnings management was analyzed in the temporal perspective, following the methodology of Gioielli (2008) who investigated the practice and timing of accounting information management by firms making initial public offerings. Initially, total accruals were estimated, followed by discretionary accruals using the modified models of Jones (1995) and Pae (2005). Panel data analysis was used to calculate coefficients for a period of eight quarters (three before, one coinciding with, and four after public offering). Our results show that firms manage accounting results by reducing them, especially in the two quarters before the quarter preceding a public offering and after the end of the lock-up period. Intended as a contribution to the discussion on earnings management, the study reveals the need for investors and Brazilian agencies regulating and inspecting capital markets to devise alternative ways of detecting and/or inhibiting opportunistic results management practices in firms making public offerings.